'Football Fitness': constraining and enabling possibilities for the management of leisure time for women. Issue 4 (8th August 2017) - Thing, Lone Friis; Hybholt, Maria Gliemann; Jensen, Andorra Lynn; Ottesen, Laila Susanne
ABSTRACT: The aim of the article is to identify constraining and enabling aspects for the management of leisure time for women participating in 'Football Fitness', a new 'sport for all programme' carried out in associative sport clubs in Denmark. The article is based on six focus group interviews with white, middle-class female participants ( N  = 32, aged 27–56). An analysis combining Hochschild's conceptualization of the second and third shift [1989. The Second Shift . New York: Avon] with Elias and Dunning's perspective on leisure as part of the spare-time spectrum and leisure sport as a quest for excitement [1986. Quest for Excitement. Sport and Leisure in the Civilizing Process . New York: Basil Blackwell] demonstrates that leisure sport participation must be understood in relation to both spare time, family life, and work life, as these spheres are interrelated. According to the women, both doing and planning housework are constraining for their leisure sport participation. On the other hand, Football Fitness is enabling in the sense that the women experience it as something pleasurable and a 'free space'.